5-Amino-2,4,6-triiodoisophthalic acid monohydrate - Beck, Tobias (International Union of Crystallography, 2008)
The title compound, C(8)H(4)I(3)NO(4)·H(2)O, shows an extensive hydrogen-bond network; in the crystal structure, molecules are linked by O—H⋯O, N—H⋯O and O—H⋯N hydrogen bonds involving all possible donors and also the water molecule.